Magnitude and contributory factors of postnatal depression: A community-based cohort study from a rural sub-district of Bangladesh - Gausia, K.; Fisher, C.; Ali, Mohammed; Oosthuizen, J. (Cambridge University Press, 2009)
Background: Recent evidence suggests that the prevalence of postnatal depression (PND) is highest in low-income developing countries. This study aimed to estimate the prevalence of PND and its associated risk factors among Bangladeshi women. Method: The study was conducted in the Matlab subdistrict of rural Bangladesh. A cohort of 346 women was followed up from late pregnancy to post-partum. Sociodemographic and other related information on risk factors was collected on structured questionnaires by trained interviewers at 34–35 weeks of pregnancy at the woman's home. A validated local language (Bangla) version of the Edinburgh Postnatal Depression Scale (EPDS-B) was used to measure depression status at 34–35 weeks of pregnancy and at 6–8 weeks after delivery. Results: The prevalence of PND was 22% [95% confidence interval (CI) 17.7–26.7%] at 6–8 weeks post-partum. After adjustment in a multivariate logistic model, PND could be predicted by history of past mental illness [odds ratio (OR) 5.6, 95% CI 1.1–27.3], depression in current pregnancy (OR 6.0, 95% CI 3.0–12.0), perinatal death (OR 14.1, 95% CI 2.5–78.0), poor relationship with mother-in-law (OR 3.6, 95% CI 1.1–11.8) and either the husband or the wife leaving home after a domestic quarrel (OR 4.0, 95% CI 1.6–10.2). Conclusions: The high prevalence of PND in the study was similar to other countries in the South Asian region. The study findings highlight the need for programme managers and policy makers to allocate resources and develop strategies to address PND in Bangladesh.